Jay Geller: The Other Jewish Question. Identifying the Jew and Making Sense of Modernity | Medaon - Lenhard, Philipp (Medaon, 2012)
Jay Geller: The Other Jewish Question. Identifying the Jew and Making Sense of Modernity, New York: Fordham University Press 2011, 510 S., ISBN: 978-0823233618, $ 35,00. Besprochen von Philipp Lenhard.